PERAN HUKUM PIDANA DALAM MENANGANI KEJAHATAN CYBER: TINJUAN TERHADAP UU ITE INSTAGRAM - Irawan, Hasdi Ade (Cahaya Ilmu Bangsa, 2024)
This research aims to analyze cyber crimes on the social media Instagram with a legal review of the ITE Law. The research method used is descriptive qualitative. The research results show that Instagram social media is one of the most widely used media in Indonesia. Apart from the positive impact of social media, Instagram also has a negative impact, one of which is cyber crime in cyberspace. Some of the crimes that exist on Instagram's sisal media are insulting and/or defaming, violating decency and spreading false and misleading news which results in consumer losses. All of these crimes have their own criminal laws. The aim of criminal law is to provide security and legal equality to society. Criminal law also has control over a criminal act because in criminal law a person who commits a criminal act is trained and given punishment according to the criminal act he or she has committed so that the person who commits the criminal act has a deterrent feeling not to trade. Apart from preventive legal protection efforts as mentioned above, of course there are also repressive efforts to tackle crime in cyberspace.